Benefits of Kalteng Berkah Scholarship, What's for and to Whom? (Evaluation of Scholarship Program Using a Transactional Model) - Bulkani, Bulkani; Kartini, Nurul Hikmah; Rahmaniati, Rita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Background: Based on the 2016-2021 Central Kalimantan Long Term Development Plan (RPJMD) contained in Regional Regulation Number 1 of 2017 (2), the vision of the Central Kalimantan provincial government is called Kalteng Berkah.